Pengaruh Adanya Undang-Undang Nomor 21 Tahun 2008 Terhadap Serta Minat Masyarakat Dalam Menabung Di Bank Syariah - Achmad Asy’ari Abdullah Toran; Dena Aji Prasetya; Halimah Citra Negoro; Achmad Maulana Fakhri; Roravianita Roravianita; Farahdinny Siswajanthy (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
For the first time in Indonesia, banking regulations have begun to be systematically regulated in Law no. 14 of 1967 which discusses the principles of banking is used as a guideline for the regulation of banking in Indonesia. In 1992, the establishment of Bank Muamalat Indonesia was the beginning of the recognition of sharia banking in Indonesia. Then with the enactment of Law no. 7 of 1992 concerning banking, as amended by Law no. 10 of 1998 explicitly discusses that in Indonesia there are two banking systems, namely conventional banking and sharia banking. The regulations regarding sharia banking in this law are considered not yet specific, therefore it is necessary to specifically establish sharia banking itself in a law, with the establishment of Law no. 21 of 2008 concerning sharia banking. For a long time, banking in Indonesia has made law no. 14 of 1967 concerning the basic principles of banking as guidelines for every bank in Indonesia. In 1992, the establishment of Bank Muamalat Indonesia was the beginning of the recognition of sharia banking in Indonesia. Then with the enactment of Law no. 7 of 1992 concerning banking, as amended by Law no. 10 of 1998 explicitly discusses that in Indonesia there are two banking systems, namely conventional banking and sharia banking. The regulations regarding sharia banking in this law are considered not yet specific, so a law that is clearer and complements the shortcomings of the previous law is needed. Therefore, Law no. 21 of 2008 concerning sharia banking. The final conclusion in this research is that the public recognizes and prefers sharia banking as regulated in Law No. 21 of 2008 because this law can explain and answer specifically the problems that exist in society regarding banking in Indonesia and with the birth of law no. 21 of 2008 is expected to provide justice and togetherness to all Indonesian people based on sharia principles which refer to Islamic law in order to achieve equal distribution of social welfare.